2013
DOI: 10.1074/mcp.m112.026708
|View full text |Cite
|
Sign up to set email alerts
|

Significant Modifications of the Salivary Proteome Potentially Associated with Complications of Down Syndrome Revealed by Top-down Proteomics

Abstract: People with Down syndrome, a frequent genetic disorder in humans, have increased risk of health problems associated with this condition. One clinical feature of Down syndrome is the increased prevalence and severity of periodontal disease in comparison with the general population. Because saliva plays an important role in maintaining oral health, in the present study the salivary proteome of Down syndrome subjects was investigated to explore modifications with respect to healthy subjects. Whole saliva of 36 Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Phosphorylated proteoforms of cardiac troponin I have been identified as candidate biomarkers for chronic heart failure by FTICR-MS (109). Orbitrap-based instrumentation has been applied to intact biomarker studies that have identified candidate proteoform biomarkers in cerebrospinal fluid for pediatric brain tumor prognosis (110) as well as multiple salivary proteoforms potentially associated with complications of Down syndrome, including early onset Alzheimer’s disease (111). Additionally, TDP has been applied to biomarker studies concerning cirrhosis at risk of malignancy (ubiquitin PTMs) (112), schizophrenia and bipolar disorder (113), neurodevelopmental disorders (in combination with MALDI MS imaging) (114), Parkinson’s disease (alpha-synuclein proteoforms) (115), and medulloblastoma and pilocytic astrocytoma (116), all in just the past two years.…”
Section: Conclusion: the Power And Promise Of The Proteoformmentioning
confidence: 99%
“…Phosphorylated proteoforms of cardiac troponin I have been identified as candidate biomarkers for chronic heart failure by FTICR-MS (109). Orbitrap-based instrumentation has been applied to intact biomarker studies that have identified candidate proteoform biomarkers in cerebrospinal fluid for pediatric brain tumor prognosis (110) as well as multiple salivary proteoforms potentially associated with complications of Down syndrome, including early onset Alzheimer’s disease (111). Additionally, TDP has been applied to biomarker studies concerning cirrhosis at risk of malignancy (ubiquitin PTMs) (112), schizophrenia and bipolar disorder (113), neurodevelopmental disorders (in combination with MALDI MS imaging) (114), Parkinson’s disease (alpha-synuclein proteoforms) (115), and medulloblastoma and pilocytic astrocytoma (116), all in just the past two years.…”
Section: Conclusion: the Power And Promise Of The Proteoformmentioning
confidence: 99%
“…The top-down MS approach can be a preferred strategy for the elucidation of PTM-associated to disease mechanisms underlying neurodegenerative disorders [163][164][165].…”
Section: Tdp In Micro-organisms Identificationmentioning
confidence: 99%
“…These results reveal apparent oral modulation of brain function during HIV infection [20]. Quantitative proteomic analysis of saliva has also been considered for the development of less invasive glucose monitoring tools in diabetic patients [21] and Down Syndrome comorbidities biomarker discovery [22]. …”
Section: Salivamentioning
confidence: 99%